Fish oil, contained in eicosapentaenoic acid and docosahexaenoic acid, attenuates testicular and spermatological damage induced by cisplatin in rats - Ciftci, O.; Cetin, A.; Aydin, M.; Kaya, K.; Oguz, F. (Wiley, 2014)
The aim of this study was to investigate the beneficial effects of the fish oil (FO) supplementation on oxidative stress, sperm characteristics and histological alterations in the male reproductive system of rats against cisplatin (CP) toxicity. The rats were divided randomly into 4 equal groups (control, FO, CP and FO+CP). FO was orally administered at the dose of 1softgel per rat per day for 14days and CP was intraperitoneally given at the dose of 7mgkg(-1) with a single injection. In CP+FO group, they were applicated at the same doses and times. The results showed that CP caused a significant oxidative damage via induction of lipid peroxidation and reduction in the antioxidant defence system potency in the testis tissue. In addition, sperm motility and sperm concentration significantly decreased but the abnormal sperm rate and histopathological testicular damage increased with CP treatment. On the other hand, FO treatment prevented oxidative, histopathological and spermatological effects of CP and reversed side effects of CP. In conclusion, FO supplementation had significant beneficial effects against CP toxicity on male reproductive system and toxic effects of CP can be prevented by FO treatment. Therefore, it appears that fish oil may be useful for the prevention and treatment of cisplatin-induced reproductive system toxicity.
Keywords: Abnormal sperm rate; cisplatin; fish oil; sperm concentration; testicular damage